1993
DOI: 10.1128/jcm.31.7.1908-1910.1993
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acanthamoeba species by Pseudomonas aeruginosa: rationale for their selective exclusion in corneal ulcers and contact lens care systems

Abstract: Cocultivation of Acanthamoeba casteUlanii and Acanthamoeba polyphaga with live Pseudomonas aeruginosa and with broth filtrates of P. aeruginosa proved equally lethal to the Acanthamoeba spp. The P. aeruginosainduced amebicidal activity is apparently toxin mediated and has two operative modes: it can function through binding ofP. aeruginosa to the ameba membrane and in the presence of one or more P. aeruginosa exoproducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 9 publications
0
25
1
Order By: Relevance
“…Similarly, the growth-promoting effect observed with E. coli agrees perfectly well with its recommended use as the growth-supporting species for Acanthamoeba, particularly during culture establishment of new environmental and clinical isolates (Schuster, 2002;Khan, 2006). On the other hand, the high consumption of P. aeruginosa ATCC 14502 associated with the high production of trophozoites adds confusion to the already published, conflicting results, since reports exist indicating that Acanthamoeba effectively feeds on this bacterium (Wang & Ahearn, 1997;Pickup et al, 2007), and that the bacterium is toxic for trophozoites (Qureshi et al, 1993). Whether the different incubation protocols and Pseudomonas strains used explain these conflicting results remains to be determined.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Similarly, the growth-promoting effect observed with E. coli agrees perfectly well with its recommended use as the growth-supporting species for Acanthamoeba, particularly during culture establishment of new environmental and clinical isolates (Schuster, 2002;Khan, 2006). On the other hand, the high consumption of P. aeruginosa ATCC 14502 associated with the high production of trophozoites adds confusion to the already published, conflicting results, since reports exist indicating that Acanthamoeba effectively feeds on this bacterium (Wang & Ahearn, 1997;Pickup et al, 2007), and that the bacterium is toxic for trophozoites (Qureshi et al, 1993). Whether the different incubation protocols and Pseudomonas strains used explain these conflicting results remains to be determined.…”
Section: Discussionmentioning
confidence: 55%
“…The contribution of different bacteria towards survival and proliferation of trophozoites has been examined in relatively few studies, using single prey/single predator incubation protocols tentatively simulating Acanthamoebagrazing activity either in soil or in water collections. While incubation in nonnutrient agar plates may simulate predator-prey interplay in soil (Pickup et al, 2007), Acanthamoeba-bacteria incubation in nonnutrient saline solutions [phosphate-buffered saline (PBS), normal saline, hypoosmolar Neff 's saline (NS)] has been used to investigate protozoan behavior in liquid environments (Bottone et al, 1992(Bottone et al, , 1994Qureshi et al, 1993;Weekers et al, 1993;Wang & Ahearn, 1997). Information available points to: (1) the selective-binding capacity of amoebae towards different species of bacteria, a feature probably involving pattern recognition and other cell-surface receptors (Allen & Dawidowicz, 1990); (2) the growth-promoting effect of certain bacteria, and, in contrast, the toxic effect of others; and (3) different food preferences of different Acanthamoeba species/isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa and Acanthamoeba species are inhabitants of soil, water, and biofilms. Free-living amoebae have been found to have an increased role as hosts to many pathogenic bacteria (Marciano-Cabral and Cabral 2003), but P. aeruginosa has been shown to inhibit growth of Acanthamoeba species (Qureshi et al 1993). To disclose the interaction between these microorganisms, we studied the effect of TTSS effector proteins on A. castellanii growth and found that the wildtype P. aeruginosa strain possessing different TTSS effector proteins and Pseudomonas strains with plasmid-mediated TTSS effector proteins killed the amoeba cells at different time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…The amoebae were clearly visible exploiting these areas of prey, but the aggregated form of this prey may have been the cause for the observed reduction in ingestion rates. Pseudomonas species are not limited to the formation of microcolonies as a defence mechanism, as some strains can be toxic to amoebae (Singh, 1945;Groscop & Brent, 1964;Qureshi et al, 1993;Weitere et al, 2005). Live cells of K. aerogenes are not known to be toxic to protozoa, and the cells did not exhibit microcolony formation within the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…microcolonies, in response to the grazing pressure (Matz et al, 2002a(Matz et al, , 2004aWeitere et al, 2005). The heat-killing process may also result in the coagulation of the bacterial cytoplasm, which has been shown to render the cells more difficult to digest (Mehlis et al, 1990), or may prevent the release of heat-labile bacterial toxins upon digestion (Groscop & Brent, 1964;Qureshi et al, 1993;Wang & Ahearn, 1997;Greub & Raoult, 2004). In addition, heat-killed cells lack the ability to express any form of cell-to-cell signalling, which might be crucial in influencing protozoanÀprey interactions, as studies have shown that bacteria have the ability to signal both positively and negatively to eukaryotic cells (Thomas & Allsopp, 1983;Joint et al, 2000).…”
Section: Introductionmentioning
confidence: 99%